The Paradox of Mu'allaq Contracts in Murabahah Financing - Putra, Panji Adam Agus; Durahman, Dani; Kurniawan, Cecep Soleh; Hatta, Muhammad (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2025)
Islamic economics requires strict adherence to contracts that comply with Sharia law, but contemporary financial practices, particularly tamlîk (purchase with ownership rights) and mu’âwadhat (reciprocal exchange) agreements, often face challenges related to gharar (excessive uncertainty), raising critical questions about their validity under Islamic law. This study focuses on resolving one of the most controversial issues in modern Islamic finance: the validity of mu’allaq contracts in murabahah financing structures. Through a normative legal approach, this study systematically analyses classical fiqh literature, fatwa from the Indonesian National Sharia Council (DSN-MUI), and regulatory guidelines such as the OJK Murabahah Guidelines, revealing fundamental differences of opinion among scholars. The validity of mu'allaq contracts in Islamic finance remains a subject of debate, with classical scholars from the Hanafi, Shafi'i, and Hanbali schools rejecting them as non-binding tabarru', while contemporary scholars permit them based on the principle of contractual freedom. This study discloses that transparent mu'allaq murabahah contracts, implemented under sharia supervision, effectively balance classical prohibitions with modern banking needs, offering sharia-compliant and practical financing solutions. By maintaining strict contractual clarity while accommodating contemporary transaction requirements, mu'allaq emerges as a contract that is legally valid and operationally beneficial for Islamic financial institutions.